A Critical Study on Awadh and Its Situation During the Mughal Raj: Exploring the geographical boundaries and administrative divisions of Awadh during the Mughal Raj (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Mughal province of Awadh extended over the territoryentirely consisting of alluvial plains, lying between 79.6o and 940 longitudeE. and 26o and 28.4 latitude N. The limits of the suba are described by AbulFazl in his Account of Twelve Provinces' It was bounded on the east by theprovince of Bihar and to the north lay the Northern mountains; sarkar Manikpurof suba Allahabad was situated on the south of the province, while on thewestern side was sarkar of Kannuj of suba Agra. The distance from sarkarGorakhpur to Kannuj was computed at 135 while only 115 kos were said toseparate the northern mountains and the southern boundary of the suba.